2022
DOI: 10.1007/s11669-022-00999-w
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the Ti-Rich Part of the Ti-Al-Nb System—Part II: High-Temperature Phase Equilibria Between 1000 and 1300 °C

Abstract: The knowledge of phase equilibria in the Ti-Al-Nb system above 1000 °C is of importance for the manufacturing of TiAl-based parts for high-temperature structural applications. Especially the extended homogeneity range of the cubic (βTi,Nb) phase, which is determined by its Al solubility, and the position and extension of the high-temperature (αTi) phase is of crucial importance for the hot-workability and microstructure control of these alloys. However, the phase diagrams reported in the literature are very co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…[ 131–136 ] This may be attributed to both the technical relevance of Nb as alloying element as well as the complex form of the Ti–Al–Nb ternary system in the composition and temperature range relevant to γ‐TiAl based alloys. This is demonstrated in Figure by isothermal sections at 700 (Figure 7a) and 1200 °C (Figure 7b) of the stated system as determined in a recent work by Distl et al [ 137,138 ] In addition to the Ti–Al related phases, further ternary intermetallic phases can occur in high Nb‐containing γ‐TiAl based alloys, i.e., the ordered ω o phase and its precursor variant [ 115,139 ] as well as the orthorhombic O phase. [ 117,140–143 ] These phases are described in more detail in the following two paragraphs, but, as can be seen in Figure 7, they are only thermodynamically stable at lower temperatures and dissolve upon heating of the material.…”
Section: Effect Of Additional Alloying Elements On the Phase Transfor...mentioning
confidence: 87%
See 2 more Smart Citations
“…[ 131–136 ] This may be attributed to both the technical relevance of Nb as alloying element as well as the complex form of the Ti–Al–Nb ternary system in the composition and temperature range relevant to γ‐TiAl based alloys. This is demonstrated in Figure by isothermal sections at 700 (Figure 7a) and 1200 °C (Figure 7b) of the stated system as determined in a recent work by Distl et al [ 137,138 ] In addition to the Ti–Al related phases, further ternary intermetallic phases can occur in high Nb‐containing γ‐TiAl based alloys, i.e., the ordered ω o phase and its precursor variant [ 115,139 ] as well as the orthorhombic O phase. [ 117,140–143 ] These phases are described in more detail in the following two paragraphs, but, as can be seen in Figure 7, they are only thermodynamically stable at lower temperatures and dissolve upon heating of the material.…”
Section: Effect Of Additional Alloying Elements On the Phase Transfor...mentioning
confidence: 87%
“…[146,152] Another ternary intermetallic phase relevant to γ-TiAl based alloys is the orthorhombic O phase with an ideal stoichiometry of Ti 2 AlNb. [6] While research work in the past sometimes distinguished between two different types of O phase, i.e., O1 and O2, which differ in their sublattice occupations, a recent work by Xu et al [153] has shown that only one of these variants actually Based on the data presented in the studies by Distl et al [137,138] corresponds to the O phase, namely O2, from a crystallographic point of view. Due to the particular stoichiometry of the O phase, it generally occurs in Al-lean and high Nb-containing alloys, e.g., see Figure 7a.…”
Section: Niobiummentioning
confidence: 99%
See 1 more Smart Citation